Association Between Fabella and Clinical Factors with Knee Osteoarthritis Severity Based on X-Ray Findings According to the Kellgren-Lawrence Classification at Royal Prima General Hospital Medan - Ricky Suryamin; Faisal Reza; Ica Y Pulungan (Medicinus, 2026)
Background: Knee osteoarthritis is a common degenerative joint disease associated with pain, functional limitation, and radiographic progression. The fabella, a sesamoid bone located in the lateral head of the gastrocnemius tendon, has been proposed as a possible contributor to knee biomechanics and osteoarthritis severity. Methods: This retrospective cohort study evaluated 274 patients who underwent knee radiographic examination at Royal Prima General Hospital Medan. The presence and condition of fabella, age, sex, and body mass index (BMI) were analyzed against knee osteoarthritis severity based on the Kellgren-Lawrence classification. Data were analyzed using univariate analysis and multiple linear regression. Result: Most patients were older than 56 years (74.8%), female (78.8%), and obese (91.2%). Fabella was non-degenerative in 47.4% of patients, degenerative in 17.9%, and not visible in 34.7%. Osteoarthritis severity was Grade II in 38.3%, Grade III in 39.4%, and Grade IV in 22.3%. Fabella (B=0.391; p<0.001) and age (B=0.337; p=0.003) were significantly associated with osteoarthritis severity, whereas sex (p=0.952) and BMI (p=0.126) were not. The overall regression model was significant (F=19.955; p<0.001; R2=0.229). Conclusions: Fabella and age were significantly associated with higher knee osteoarthritis severity, while sex and BMI were not significant predictors in this cohort. Radiographic assessment of fabella may provide additional information in evaluating patients with knee osteoarthritis.